2019
DOI: 10.1016/j.ebiom.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-specific amplitude-modulated radiofrequency electromagnetic fields induce differentiation of hepatocellular carcinoma via targeting Cav3.2 T-type voltage-gated calcium channels and Ca2+ influx

Abstract: Background Administration of amplitude modulated 27·12 MHz radiofrequency electromagnetic fields (AM RF EMF) by means of a spoon-shaped applicator placed on the patient's tongue is a newly approved treatment for advanced hepatocellular carcinoma (HCC). The mechanism of action of tumour-specific AM RF EMF is largely unknown. Methods Whole body and organ-specific human dosimetry analyses were performed. Mice carrying human HCC xenografts were exposed to AM RF EMF using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…We previously reported that cellular calcium flux was affected by low energy electromagnetic fields, which were amplitude-modulated at specific frequencies [[24], [25], [26]]. In our study of hepatocellular carcinoma, we discovered that T-type voltage gated calcium channels (VGCC) mediate hepatocellular carcinoma specific AM RF EMF cell growth inhibition of hepatocellular carcinoma cell lines and xenografts [13]. Therefore, we treated breast cancer cells with ethosuximide, a pan T-type VGCC inhibitor, and found that the growth suppressive effect of BCF was significantly abrogated (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that cellular calcium flux was affected by low energy electromagnetic fields, which were amplitude-modulated at specific frequencies [[24], [25], [26]]. In our study of hepatocellular carcinoma, we discovered that T-type voltage gated calcium channels (VGCC) mediate hepatocellular carcinoma specific AM RF EMF cell growth inhibition of hepatocellular carcinoma cell lines and xenografts [13]. Therefore, we treated breast cancer cells with ethosuximide, a pan T-type VGCC inhibitor, and found that the growth suppressive effect of BCF was significantly abrogated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The exposure system RF output was set for delivery of a SAR level of 255 mW/kg within the brain. This SAR was selected so that it is 1) within the range of previously demonstrated in vitro activity (30–400 mW/kg) [16] and 2) within the range of wbSAR1g and psSAR1g in patients receiving treatment with the TheraBionic device (1–352 mW/kg) [13]. All study protocols were approved by the Wake Forest Institutional Animal Care and Use Committee (IACUC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…T-type Ca 2+ channels (T-channels) can be activated by small depolarizations of the plasma membrane and have been implicated in a variety of physiological processes, including fertilization, neuronal firing, cancer therapy, hormone secretion and muscle fiber development [8][9][10][11][12] . Bijlenga 13 .…”
Section: Introductionmentioning
confidence: 99%
“…T-type voltage-operated Ca 2+ channels may also be involved in regulating the proliferation and differentiation of liver cancer stem cells. Radiofrequency electromagnetic fields have been shown to induce tumor shrinkage in several cancers, including HCC (treatment options, Figure 4 ) [ 14 ]. In a study of the mechanisms involved, employing mouse HCC xenograft tumors and Huh-7 liver cells, Jimenez and colleagues found that the application of an amplitude modulated radiofrequency electromagnetic field (optimized for treatment of HCC tumors), increases Ca 2+ entry to HCC cells via T-type voltage-operated Ca 2+ channels, resulting in an increase in [Ca 2+ ] cyt and cell death.…”
Section: Voltage-operated Ca 2+ Channels Insp mentioning
confidence: 99%